An improved preparation of phorbol from croton oil - Pagani, Alberto; Gaeta, Simone; Savchenko, Andrei I.; Williams, Craig M.; Appendino, Giovanni (Beilstein Journal of Organic Chemistry, 2017)
Background: Croton oil is the only commercial source of the diterpenoid phorbol (1a), the starting material for the semi-synthesis of various diesters extensively used in biomedical research to investigate cell function and to evaluate in vivo anti-inflammatory activity. While efficient chemoselective esterification protocols have been developed for phorbol, its isolation from croton oil is technically complicated, and involves extensive manipulation of very toxic materials like the oil or its native diterpenoid fraction.Results: The preparation of a crude non-irritant phorboid mixture from croton oil was telescoped to only five operational steps, and phorbol could then be purified by gravity column chromatography and crystallization. Evidence is provided that two distinct phorboid chemotypes of croton oil exist, differing in the relative proportion of type-A and type-B esters and showing different stability to deacylation.Conclusion: The isolation of phorbol from croton oil is dangerous because of the toxic properties of the oil, poorly reproducible because of differences in its phorboid profile, and time-consuming because of the capricious final crystallization step. A solution for these issues is provided, suggesting that the poor-reproducibility of croton oil-based anti-inflammatory assays are the result of poor quality and/or inconsistent composition of croton oil.
Keywords: croton oil; diterpenoids; natural products; phorbol; transesterification

Hagers Handbuch der Pharmazeutischen Praxis - Gläser, S.; Winter, A.; Hecker, E. (Crotonis oleum (Crotonöl), 1998)

(untitled) - Meyer-Bertenrath, J. G. (Experientia, 1969)

(untitled) - Orra, S.; Waltzman, J. T.; Mlynek, K.; Duraes, E. F. R.; Kundu, N.; Zins, J. E. (Plast. Reconstr. Surg., 2015)

(untitled) - Pelletier, J.; Caventou, J. B. (J. Pharm., 1818)

(untitled) - Böhm, R.; Flaschenträger, B. (Naunyn-Schmiedeberg's Arch. Pharmacol., 1930)

(untitled) - Hecker, E.; Schmidt, R. (Prog. Chem. Org. Nat. Prod., 1974)

(untitled) - Pettersen, R. C.; Ferguson, G.; Crombie, L.; Games, M. L.; Pointer, D. J. (Chem. Commun., 1967)

(untitled) - Berenblum, I. (Cancer Res., 1941)

(untitled) - Newton, A. C. (Chem. Rev., 2001)

(untitled) - Han, Z. T.; Zhu, X. X.; Yang, R. Y.; Sun, J. Z.; Tian, G. F.; Liu, X. J.; Cao, G. S.; Newmark, H. L.; Conney, A. H.; Chang, R. L. (Proc. Natl. Acad. Sci. U. S. A., 1998)

(untitled) - Appendino, G. (Prog. Chem. Org. Nat. Prod., 2016)

(untitled) - Boyle, G. M.; d'Souza, M. M. A.; Pierce, C. J.; Adams, R. A.; Cantor, A. S.; Johns, J. P.; Maslovskaya, L.; Gordon, V. A.; Reddell, P. W.; Parsons, P. G. (PLoS One, 2014)

(untitled) - Crombie, L.; Games, M. L.; Pointer, D. J. (J. Chem. Soc. C, 1968)

(untitled) - Pieters, L. A.; Vlietnick, A. J. (Planta Med., 1986)

(untitled) - Marshall, G. T.; Douglas Kinghorn, A. (J. Chromatogr., 1981)

(untitled) - Mishra, N. C.; Estensen, R. D.; Abdel-Monem, M. M. (J. Chromatogr., 1986)

(untitled) - Bertolini, T. M.; Giorgione, J.; Harvey, D. F.; Newton, A. C. (J. Org. Chem., 2003)

(untitled) - Cairnes, D. A.; Mirvish, S. S.; Wallcave, L. (Cancer Lett., 1981)

(untitled) - Seebach, D.; Thaler, A.; Beck, A. K. (Helv. Chim. Acta, 1989)

(untitled) - Tseng, S.-S.; Van Duuren, B. L.; Solomon, J. J. (J. Org. Chem., 1977)

(untitled) - Schmidt, R.; Hecker, R. (Cancer Res., 1975)

(untitled) - Tubaro, A.; Dri, P.; Delbello, G.; Zilli, C.; Della Loggia, R. (Agents Actions, 1986)

(untitled) - Bauer, R.; Tittel, G.; Wagner, H. (Planta Med., 1983)

Deceptions of World War II - Breuer, W. B. (Wiley & Sons, 2002)

Dubious Battle - Steinbeck, J. (Penguin Books, 2006)

Naturally Occurring Phorbol Esters - Evans, F. I. (Phorbol: Its Esters and Derivatives, 1986)